A qualitative approach to study social perceptions and public policies in dehesa agroforestry systems. (15th December 2016) - Gaspar, P.; Escribano, M.; Mesias, F.J.
Highlights: Focus group has revealed is a suitable tool for the study of agroforestry systems. Agroforestry systems generate commercial and environmental values. D ehesas are mainly identified as suppliers of high-quality animal food products. Certain mechanisms should be established to compensate ecosystem service suppliers. Abstract: Agroforestry systems, which include woodlands, pasturelands and various livestock species, are multifunctional systems that must be productive in order to guarantee their conservation, as well as their provision of services such as the maintenance of the landscape and/or cultural uses. These systems generate commercial and environmental values, which are not always perceived by the society. It is therefore necessary to analyse the value society places in agroforestry systems, with a special focus on the dehesa system as a paradigmatic example. The information has been obtained from 4 focus groups organised in Badajoz and Caceres (Spain) in May/June 2015. The discussions involved 35 people with an even distribution of age and gender being sought for each group. The results of the study revealed a lack of citizen familiarity with the agroforestry system, as well as of the services it supplies, besides those that are purely associated to food production. Other key findings were the low importance given by the consumers to the item "production system" – a key aspect in order to valorize the products derived from these systems – as well as the difficulty perceived by the citizens in finding a compensation for the proprietors of these systems as suppliers of ecosystem-related services. In summary, it has become clear that it is necessary to implement specific policies and complement the existing ones so that system proprietors can be financially remunerated for the services supplied to the society, although citizen awareness must also be reinforced so that they become conscious of the goods they receive from the agrosystems and therefore understand their value.